2020
DOI: 10.1016/j.jpubeco.2020.104249
|View full text |Cite
|
Sign up to set email alerts
|

The long-term effects of childhood exposure to the earned income tax credit on health outcomes

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 35 publications
2
34
0
1
Order By: Relevance
“…Indeed, we found that out of the ten studies that did consider the mechanisms (i.e. Bitler, 2004;Boyd-Swan et al, 2016;Braga et al, 2019;Evans and Craig, 2014;Gregg et al, 2009;Grip et al, 2012;Harkness, 2016;Milligan and Stabile, 2009;Williams, 2020), income was an important factor mediating the policy effects on mental health. In addition, because some of policies in the reviewed studies included a work component (i.e.…”
Section: Evidence Gaps and Areas For Future Researchmentioning
confidence: 97%
See 2 more Smart Citations
“…Indeed, we found that out of the ten studies that did consider the mechanisms (i.e. Bitler, 2004;Boyd-Swan et al, 2016;Braga et al, 2019;Evans and Craig, 2014;Gregg et al, 2009;Grip et al, 2012;Harkness, 2016;Milligan and Stabile, 2009;Williams, 2020), income was an important factor mediating the policy effects on mental health. In addition, because some of policies in the reviewed studies included a work component (i.e.…”
Section: Evidence Gaps and Areas For Future Researchmentioning
confidence: 97%
“…Increases in both earnings-related eligibility and generosity for this J o u r n a l P r e -p r o o f benefit were evaluated by eight studies in the review. Six of these studies focused on working-age adult outcomes (Boyd-Swan et al, 2016;Braga et al, 2019;Evans and Craig, 2014;Gangopadhyaya et al, 2019;Lenhart, 2019;Rambotti, 2020), with the remaining two studies focusing on children (Averett and Wang, 2018;Hamad and Rehkopf, 2016).…”
Section: Expanding the Usa Earned Income Tax Credit (N=8)mentioning
confidence: 99%
See 1 more Smart Citation
“…This study contributes to a small but growing literature examining the spillover health benefits of the EITC program (Evans & Garthwaite, 2014; Boyd‐Swan et al, 2016; Hoynes et al, 2015; Braga et al, 2019; Dow et al, 2019; Strully et al 2010). Evans and Garthwaite (2014) and Boyd‐Swan et al (2016) have previously documented the impact of the expansion of the federal EITC program on maternal health of nonelderly adult women following the Omnibus Budget Reconciliation Acts of 1990 and 1993.…”
Section: Existing Literature and Contributionsmentioning
confidence: 99%
“…Kuka and Shenhav (2020) use linked CPS and Social Security administration data and a research design that uses both EITC expansions and the timing of a woman's first birth, finding that mothers who were exposed to an EITC expansion when their children were younger were more likely to become employed than those first exposed when their children were somewhat older. The EITC's impact has also been widely studied along other dimensions, including its (small) effects on marriage and fertility (Dickert-Conlin & Houser 2002;Holtzblatt & Rebelein 2000;Michelmore 2014;Baughman & Dickert-Conlin 2009), its effects on economic indicators of economic self-sufficiency in disadvantaged neighborhoods (Neumark, Asquith & Bass 2019), its ability to improve health outcomes among infants as well as mothers (Evans & Garthwaite 2014;Baughman & Duchovny 2016;Hoynes, Miller & Simon 2015), and its positive impacts on children's school test scores and educational attainment (Dahl & Lochner 2012;Chetty, Friedman & Rockoff 2011), as well as college enrollment (Bastian & Michelmore 2018;Manoli & Turner 2018) and adult health (Braga, Blavin & Gangopadhyaya 2020). It has also been shown to have only a small impact on hours worked among those already employed (Saez 2010), but instead most of the impact on labor supply comes through moving individuals from not working to working.…”
Section: Background On the Eitcmentioning
confidence: 99%